Epileptiform activity index for assessing oxcarbazepin therapy of newly-diagnosed focal epilepsy in adolescents and adults - V. A. Karlov; A. B. Kozhokaru; P. N. Vlasov; T. N. Pushkar; A. S. Orlova (Эпилепсия и пароксизмальные состояния)
Introduction. Oxcarbazepine (OXC) is approved for initial and adjunctive therapy of focal epilepsy (FE), being also a drug of choice in case of pediatric FE. Despite that OXC has been used in the Russian Federation (RF) since 2007, studies assessing its efficacy and tolerability are scarce.Aim. To evaluate efficacy and tolerability of OXC therapy in patients with newly-diagnosed epilepsy.Patients and methods. There were enrolled 103 patients (56 (54.4%) into the study: males and 47 (45.6%) females with FE, aged 44.32±19.71 years. Depending on the OXC daily dose, all patients were divided into 3 subgroups: <1200 mg/ day (n=20; 19.4%); 1200 mg/day (n=67; 65.1%), and > 1200 mg/day (n=16; 15.5%). Video-electroencephalographic (video-EEG) monitoring was performed at each visit (at baseline, 1, 3, 6 and 12 months after then onset of therapy). Treatment efficacy was assessed by using the criteria of retention on treatment, seizure absence, seizure rate decrease by >50%, seizure rate decrease by <50% (insufficient efficacy). Adverse effects (AEs) were assessed in accordance to the Side Effects of Anti-Epileptic Drugs (SIDAED) treatment scale and emerging pharmacodynamics aggravation (increased seizure rate compared to baseline/emergence of new seizure type).Results. It was found that retention on OXC monotherapy during the 12-month follow-up period was achieved in 69.0% (n=71) patients, among which 15.5% (n=16) received less than OXC at dose of 1200 mg/day, 44.7% (n=46) - 1200 mg/ day, and 8.8% (n=9) - more than 1200 mg/day, respectively. Total rate of intolerable AEs during the follow-up period was 13.6% (n=14). Comparing initial vs. 12-month timepoint EAI magnitude after the onset of OXC therapy revealed that it was significantly decreased by 6.9-fold (p<0.05).Conclusions. OXC is an effective drug for the initial treatment of FE in adolescents and adults highlighted with favorable tolerability profile. 12-month follow-up monitoring demonstrated that EAI was reduced almost by 7-fold allowing to consider it as an objective quantitative marker for assessing treatment efficacy.